Syncarcinogenesis of natural UV radiation and polycyclic aromatic hydrocarbons in the development of squamous cell carcinomas of the skin? - Weistenhöfer, Wobbeke; Lutz, Regina; Hiller, Julia; Schmitz-Spanke, Simone; Drexler, Hans (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Squamous cell carcinomas (SCC) of the skin can be induced by occupational exposures to polycyclic aromatic hydrocarbons (PAHs), as in tar and soot, or to UV radiation and can be recognized and compensated as occupational diseases. A possible syncarcinogenic effect of these exposures in the development of SCC in humans is under discussion. For the scientific validation of this question, a systematic literature search was conducted using the databases PubMed, Web of Science, and Scopus. Studies on individuals with SCC of the skin and their precursors as well as occupational, non-occupational, or therapeutic exposure to UV radiation and PAHs were selected. In addition, animal studies with exposure to UV radiation and PAHs were evaluated. After screening the abstracts of 510 identified studies, the full texts of 131 studies were reviewed. None of the epidemiological studies provided robust evidence for a syncarcinogenesis of PAHs and UV radiation in the development of SCC of the skin in humans. Nevertheless, as there are indications for a (super-)additive effect of UV radiation and PAH exposure from animal studies and mechanistic investigations, syncarcinogenesis seems possible. However, quantitative dose-response relationships are lacking which would allow comparison of the onset of an adverse effect between the different exposure levels.
CRIS-Team Scopus Importer:2022-09-16